The tadpole of Rhinella proboscidea (Anura: Bufonidae) with notes on adult reproductive behavior - Menin, Marcelo; Rodrigues, Domingos J.; Lima, Albertina P. (Zootaxa, 2006)
The tadpoles of Rhinella proboscidea are described and compared with other tadpoles of the Rhinella margaritifer group. The tadpole of R. proboscidea is characterized by small size (17.8 mm), tooth row formulae 2(2)/3, oral papillae only on lateral margins, jaw sheath V-shaped, spiracle sinistral, vent tube medial, body oval in dorsal view and depressed in lateral view, and color in life light brown. Tadpoles of R. proboscidea are morphologically similar to other species within this group and closely resemble those of R. margaritifer from Cusco Amazónico and R. castaneotica from Pará, Brazil. Rhinella proboscidea is an explosive breeder and reproduction occurs in temporary pools or small headwaters of streams or soaks, during the rainy season.